Regard sur l’éducation relative à l’environnement des adultes - Carine Villemagne (VertigO)
Environmental adult education is difficult to capture. Environmental adult education practices are little documented and theoretical proposals are very few. However adults must be considered as a priority population as far as contemporary environmental problems which need emergency solutions are concerned. Taking support on a scientific literature review, we approach environmental adult education according to two dimensions. First, we explore two main roles of adult: adult as a citizen and as learner, because of possible influences of these two roles on environmental education. Second, we draw up a picture of environmental adult education. Various contexts of this field will be investigated with support of Quebecois examples. Existing theoretical proposals of environmental adult education will be then presented and discussed.